Estudo da performance do doppler da artéria oftálmica e modelo fullpiers como métodos preditores de desfechos adversos em mulheres com pré-eclâmpsia - Naves, Welington Ued (2024)
Objective: To assess the role of ophthalmic artery Doppler (OAD) indices alone and in combination with the multivariate model using the fullPIERS model score in predicting adverse maternal outcomes in pregnant women hospitalized for pre-eclampsia with signs and symptoms of clinical deterioration with target organ involvement. Methods: This was an inter-institutional prospective cohort study in which pregnant women hospitalized with a diagnosis of pre-eclampsia associated with signs and symptoms of clinical deterioration with target organ involvement were recruited. Maternal outcomes were grouped into five groups and classified binarily (present or absent). All the pregnant women underwent OAD of both eyes, with calculation of the mean of the following continuous parameters: resistance and pulsatility indices (RI and PI), peak velocity systolic (PVS), end-diastolic velocity (EDV), second peak velocity systolic (P2) and peak velocity ratio (PVR), as well as calculation of the fullPIERS score. Comparisons of means between continuous variables and outcomes were made using the Student's t-test. The chi-square test was used to study the correlation between the parameters and the maternal outcomes, based on the established cut-off points. For significant correlations, the ODDS Ratio and ROC (receiver operating characteristic) curves were calculated to establish the sensitivity, specificity, positive and negative predictive value of the continuous variables in predicting maternal outcomes. Results: Significant associations were found between the OAD indices: first peak systolic velocity (P1), second peak systolic velocity (P2) and end-diastolic velocity (EDV) with blood pressure levels above 160 x 110 mmHg (hypertensive crisis), respectively with significance levels of p=0. 0001, p<0.0001, p<0.0001 and P1, P2 and EDV with the sum of all outcomes with respective significance levels of p=0.005, p=0.0001 and p=0.0019. The other Doppler indices showed no association with the outcomes analyzed. Conclusion: The Doppler indices of the ophthalmic arteries, P1, P2 and EDV alone and associated with the multivariate model using the fullPIERS score are accurate in predicting adverse maternal outcomes such as hypertensive crisis, liver damage and the sum of outcomes.